Puerarin Alleviates Depression-Like Behavior Induced by High-Fat Diet Combined With Chronic Unpredictable Mild Stress via Repairing TLR4-Induced Inflammatory Damages and Phospholipid Metabolism Disorders - Gao, Li-Na; Yan, Maocai; Zhou, Lirun; Wang, Jian’an; Sai, Chunmei; Fu, Yingjie; Liu, Yang; Ding, Lin (Frontiers in Pharmacology, 2021)
Puerarin has been reported as potential agent for neuro-inflammatory disorders. However, there have been no reports of using puerarin for the treatment of depression based on Toll-like receptor 4 (TLR4)-mediated inflammatory injury. In this study, we evaluated the protective effects of puerarin on depression-like rats induced by high-fat diet (HFD) combined with chronic unpredictable mild stress (CUMS). The mechanism was screened by lipidomics, molecular docking and confirmed by in vivo tests. Puerarin treatment significantly improved 1% sucrose preference and ameliorated depression-like behavior in open-field test. The anti-depressive effects of puerarin were associated with decreased pro-inflammatory cytokines production, including interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α), and increased anti-inflammatory cytokine level (IL-10) in rat hippocampal tissues and plasma. Hematoxylin-eosin (H&E), immunofluorescence staining and Western blotting results displayed that puerarin alleviated inflammatory injury by suppressing TLR4 expression and by repairing intestine mucus barrier via enhancing the expression of claudin-1 and occludin. Non-targeted lipidomics analysis showed that the most significant difference metabolites modified by puerarin were phospholipids. Puerarin treatment altered biomarkers were identified as PC (15:1/20:1), PE (15:1/16:1) and PI (18:2/20:1) in comparison with HFD/CUMS group. Molecular docking modeling revealed that puerarin could bind with cytosolic phospholipase A2 (cPLA2) and cyclooxygenase-2 (COX-2), which play central roles in TLR4-mediated phospholipid metabolism. In vivo, puerarin treatment decreased enzyme activities of cPLA2 and COX-2, resulting in lower production of prostaglandin E2 (PGE2) in hippocampal and intestinal tissues. In conclusion, puerarin treatment reverses HFD/CUMS-induced depression-like behavior by inhibiting TLR4-mediated intestine mucus barrier dysfunction and neuro-inflammatory damages via TLR4/cPLA2/COX-2 pathway.